Предмет: Алгебра,
автор: Сейсель
1)-5 (3а+1)-11=-16
2)3(х-5)+10=2 (3+х)-14
Ответы
Автор ответа:
0
1)-5 (3а+1)-11=-16
-15a - 5 - 11 = -16
-16a = -16 + 16
16a = 0
a = 0
2)3(х-5)+10=2 (3+х)-14
3x - 15 + 10 = 6 + 2x - 14
3x - 2x = 6 - 14 + 15 - 10
x = -3
-15a - 5 - 11 = -16
-16a = -16 + 16
16a = 0
a = 0
2)3(х-5)+10=2 (3+х)-14
3x - 15 + 10 = 6 + 2x - 14
3x - 2x = 6 - 14 + 15 - 10
x = -3
Похожие вопросы
Предмет: Биология,
автор: nikgts474
Предмет: Биология,
автор: galeevaalyna
Предмет: Математика,
автор: milashekKsu
Предмет: Обществознание,
автор: чоапдлпошмщп